Nilai-Nilai Kepemimpinan Islam oleh Kepala Sekolah di Sekolah Dasar Negeri - Rahmi Rahmatillah (STIT Muhammadiyah Bangil Pasuruan, 2024)
The quality of leadership determines the success of an institution or organization. So a leader must be able to manage, administer and move an organization effectively and appropriately. A leader must also be wise in making every decision. Leadership is a person's ability to convince and influence other people so that they voluntarily work and are invited to carry out their will or ideas. The aim of this research is to examine the application of Islamic leadership values ​​in the school environment which will have an impact on the formation of an educational culture, and the challenges that occur when the application of Islamic leadership values ​​at SDN Tegallega 2 Bogor is implemented. The research method used is a descriptive method with a qualitative approach. The location of the research was at SDN Tegallega 2 Bogor. Data was obtained by interviewing the principal of SDN Tegallega 2 Bogor and observing the school studied. The research results show that the leadership at SDN Tegallega 2 Bogor has Islamic leadership values ​​that are in accordance with the teachings of the Islamic religion. The criteria and characteristics that a leader needs to have are fairness, amanah (responsibility), fathonah (intelligent), tabligh (conveying), shiddiq (honest), and uswah (exemplary). Islamic leadership values ​​such as honesty, responsibility, justice, deliberation and caring are important guidelines for overcoming various challenges and problems. This is in accordance with the teachings of the Islamic religion which is guided by the Al-Quran and also the example set by the Prophet Muhammad SAW in leading.